Large-scale geomagnetic field disturbances accompanied by the powerful explosion of the Tonga volcano on January 15, 2022. - Chernogor, L. F.; Holub, M. Yu. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2022)
Background. A number of authors have described the results of observations of variations in the geomagnetic field caused by the Tonga volcano explosion. The main attention was paid to the analysis of quasi-periodic processes, disturbance of the neutral wind system, ionospheric currents at the heights of the dynamo region of the atmosphere. Temporal variations of the geomagnetic field observed at a number of the Intermagnet network magnetic stations remote from the volcano were described. A more detailed analysis of the magnetic effect of the Tonga volcano is an urgent task.The purpose of this paper is to analyze the large-scale disturbances of the geomagnetic field caused by the powerful explosion of the Tonga volcano, which took place on January 15, 2022.Techniques and Methodology. The data of measurements on the global network of Intermagnet magnetic stations were used for the analysis. These stations were located on different sides of the disturbance source. The X-, Y-, and Z-components of the geomagnetic field were subjected to analysis. The time resolution was 1 min, the error did not exceed 1 nT. Temporal variations of the geomagnetic field level from January 12 to January 18, 2022, were analyzed. The most magnetically quiet days were January 13 and January 17, 2022. They were used as reference days.Results. As a result of the time variations analysis of the X-, Y-, and Z-components of the geomagnetic field registered at stations located at a distance from ~ 2000 to 8000 km from the epicenter of the Tonga volcano explosion, it was established that the geomagnetic effect was of a global nature. Six groups of geomagnetic field component disturbances that could have been caused by a volcanic explosion were identified. Speeds close to ~ 4 and 1.5 km/s are characteristic of MHD waves. A speed close to ~ 1 km/s is typical for a blast wave. A speed of ~ 500 m/s have atmospheric gravity waves. Disturbances with speeds of ~ 315 and 200 m/s apparently propagated by Lamb waves and tsunamis. The amplitude of quasi-periodic disturbances of the geomagnetic field was estimated to be 1–10 nT. These values are in good agreement with the observation results. Estimates of the magnitude of aperiodic disturbances gave a value of 30–60 nT, which also agreed with the measurement results.Conclusions. It was confirmed that the powerful explosion of the volcano led to the disturbance of all subsystems in the Earth – atmosphere – ionosphere – magnetosphere system.